2020
DOI: 10.1371/journal.pone.0242062
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factor VIII, white matter hyperintensities and cognitive function: Results from the Cardiovascular Health Study

Abstract: Objective To investigate the relationship between high FVIII clotting activity (FVIII:C), MRI-defined white matter hyperintensities (WMH) and cognitive function over time. Methods Data from the population-based Cardiovascular Health Study (n = 5,888, aged ≥65) were used. FVIII:C was measured in blood samples taken at baseline. WMH burden was assessed on two cranial MRI scans taken roughly 5 years apart. Cognitive function was assessed annually using the Modified Mini-Mental State Examination (3MSE) and Digit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…FVIII levels increase in acute stroke ( 107 ) and generally with age ( 108 ), in addition to their association with increased VaD risk ( 104 – 106 ). However, a recent study found no strong association between FVIIIa clotting activity and cognitive function or burden of white matter hyperintensities on magnetic resonance images ( 109 ). Although this study did not specifically look at VaD, as previously discussed, white matter damage is one of the hallmarks of VaD and SVD ( 79 ).…”
Section: Coagulation and Complement Systems In Vascular Dementiamentioning
confidence: 99%
“…FVIII levels increase in acute stroke ( 107 ) and generally with age ( 108 ), in addition to their association with increased VaD risk ( 104 – 106 ). However, a recent study found no strong association between FVIIIa clotting activity and cognitive function or burden of white matter hyperintensities on magnetic resonance images ( 109 ). Although this study did not specifically look at VaD, as previously discussed, white matter damage is one of the hallmarks of VaD and SVD ( 79 ).…”
Section: Coagulation and Complement Systems In Vascular Dementiamentioning
confidence: 99%